Use the FOLD method<span>
(a+b)(c+d)=ac+ad+bc+bd
</span><span>−12<span>s<span><span>^2 </span><span></span></span></span>+ 3st + 8ts − 2<span>t<span><span>^2</span><span>
</span></span></span></span>Collect like terms
-12{s}^{2}+(3st+8st)-2{t}^{2}
Simplify
<span>-12{s}^{2}+11st-2{t}^{2}<span>−12<span>s<span><span>2</span><span></span></span></span>+11st−2<span>t<span><span>2
The answer is = -12s^2 + 11st - 2t^2</span></span></span></span></span>
I would subtract the 2nd from the first one
so -4x - -2x = -2x
4y - 4y = 0
-20 - -2 = -18
-2x = -18
now I would divide that by -2 to get the value for x
so no we have x = 9
now you just have to substitute that into one of the equations and simplify to get y
-2 X 9 + 4y = -2
-18 + 4y = -2
4y =16
y = 4
J because this is a quadratic function which is shaped like a u upward
Answer:
Acute angle, right angle, obtuse angle and reflex angle.
Step-by-step explanation:
Acute angle -
0° < θ < 90°
Right angle -
θ = 90°
Obtuse angle -
90° < θ < 180°
Reflex angle -
θ > 180°
We can't tell from the graph whether the left point of each step is included, or the right point. If the left, this is a graph of
y = 7 + floor(x)